Evaluation of the effectiveness of potential biocontrol yeasts against black sur rot and ochratoxin A occurring under greenhouse and field grape production conditions - Ponsone, María Lorena (2016)
The efficacy of two strains of Lanchancea thermotolerans in preventing the growth and ochratoxin A (OTA) accumulation of ochratoxigenic fungi under greenhouse and field conditions were evaluated during three consecutive year trials. The data from this study showed that both yeast strains were able to control Aspergillus section Nigri species ochratoxin A accumulation in wine grapes at harvest stage. The nhibitory effects were dependent on the ochratoxigenic species, yeast strains, and year analyzed. Over all conditions assayed, ochratoxin A accumulation was reduced from 27% to 100%, depending on the conditions evaluated. These results are promising for future development of a bio-pesticide.